Learning Obstacles in the Concept of Quadrilateral Constructed Areas - Soneta, Vidya; ., Nurjanah; Prabawanto, Sufyani (KnE Social Sciences, 2024)
This study aims to describe the learning obstacle in the concept of quadrilateral constructed areas based on the meaning obtained by students. The research method used is a qualitative method with a case study design. The participants in the research were 26 students of grade VII from one of the Bungo State Junior High Schools. The data collection was carried out by testing the respondents’ abilities, interviewing them, and then conducting an in-depth analysis of the obstacles experienced by students. Based on the research conducted, it was revealed that epistemological obstacles arise because students understanding about the given problem is different from the usual context. Epistemological obstacle arise in the form of students’ limited knowledge in solving problems related to the concept of the area of a rectangular dataset. Ontogenic obstacles are related to students’ lack of concentration and readiness in the teaching and learning process. Keywords: junior high schools, learning obstacles, quadrilateral constructed areas